Energy economics - Pepermans, Guido, ....-; Morbee, Joris, ....-; Ovaere, Marten, ....- (Leuven : Acco, 2019)
Energy Economics is primarily a textbook for engineering, business and economics students who wish to develop an economic understanding of current energy issues. It can also serve as a reference book for a wider interdisciplinary audience, such as scientists with a basic knowledge of economics. Using simple economic models, the book analyzes the strategy and behavior of the key players in the energy market. The objective is to help the reader understand the institutions and driving forces of energy markets, recognize the motives behind policies such as price controls and environmental regulations, assess their costs and benefits, and ultimately make well-founded business and policy decisions in the energy field. The main topics covered in the book are the history and future of energy use, the optimal use of non-renewable energy resources, the economics of the environment, energy efficiency and climate change, and the functioning of the markets for coal, oil, gas, electricity and renewables.
Keywords: Energiemanagemnt ; economie